2020
DOI: 10.1111/jnu.12585
|View full text |Cite
|
Sign up to set email alerts
|

The Enabling, Enacting, and Elaborating Factors of Safety Culture Associated With Patient Safety: A Multilevel Analysis

Abstract: Purpose Worldwide, 1 in 10 hospital patients is harmed while receiving care. Despite evidence that a culture of safety is associated with greater patient safety, these effects and the processes by which safety culture impacts patient safety are not yet clearly understood. Therefore, the purpose of this study was to examine the effects of various safety culture factors on nurses’ perceptions of patient safety using an innovative theoretical model. Design This descriptive, correlational study drew on deidentifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 23 publications
2
24
0
9
Order By: Relevance
“…In this regard, the significance of achieving a positive patient safety culture and patient safety has been continuously emphasized [ 5 , 6 ]. Patient safety culture is a crucial part of organizational culture in which healthcare providers recognize patient safety performance as the highest priority measure to prevent patient harm [ 3 , 7 ]. Furthermore, patient safety culture includes the manner in which healthcare providers are expected to behave, what attitudes and activities are appropriate, and what patient safety procedures are rewarded or prohibited [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the significance of achieving a positive patient safety culture and patient safety has been continuously emphasized [ 5 , 6 ]. Patient safety culture is a crucial part of organizational culture in which healthcare providers recognize patient safety performance as the highest priority measure to prevent patient harm [ 3 , 7 ]. Furthermore, patient safety culture includes the manner in which healthcare providers are expected to behave, what attitudes and activities are appropriate, and what patient safety procedures are rewarded or prohibited [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare professionals' perceptions of safety culture and their association with patient safety have been examined in hospitals around the world, for example, in Canada [5], the United States [6], the Netherlands [7], Jordan [8], Taiwan [9], China [10,11], and Saudi Arabia [12]. Although safety culture has been linked with patient safety outcomes, a recent literature review revealed that research findings regarding these relationships have been inconsistent [13].…”
Section: Introductionmentioning
confidence: 99%
“…Para a análise dos dados, seguiu-se a proposta da Análise de conteúdo na modalidade temática, a qual "consiste em descobrir os núcleos de sentido que compõem uma comunicação, cuja presença ou frequência signifiquem alguma coisa para o objeto analítico visado" 15 . Assim, desta análise, emergiram três categorias, tomando por referência o modelo teórico (Figura 1) que foi elaborado a partir da tríade de Donabedian 16 e do modelo "Capacitando, Colocando em prática e Elaborando a CSP" [12][13]17 Nesta categoria, tem-se comportamento, práticas organizacionais e ações da liderança para um cuidado seguro. Estes são considerados como "aspectos capacitantes da CSP" que levam a redução dos erros, priorizando a segurança e criando um ambiente onde os profissionais podem colocar em prática a SP através da adoção de práticas mais seguras 13 .…”
Section: Os Participantes Foram Esclarecidos Quanto à Pesquisa E Assinaram O Termo Deunclassified
“…Sabe-se que o apoio da gestão hospitalar e da média gerência são fundamentais para que as melhorias ocorram, pois são os líderes que devem apontar os caminhos, direcionar as ações, bem como prover os meios para que isso seja alcançado. O apoio da liderança serve de base para a criação e manutenção da CSP [12][13]17 . Uma liderança engajada e consciente da importância da SP consegue criar um contexto acolhedor para melhorias em sua instituição, ao mesmo tempo que busca corrigir aspectos inadequados do contexto de forma mais abrangente.…”
Section: Expectativas E Ações De Promoção De Segurança Dos Supervisores/gerentesunclassified